RECONSTRUCTION OF EXTREME PALEOCLIMATIC EVENTS IN NORTHWESTERN SIBERIA USING ANCIENT WOOD FROM FORT NADYM - G. T. Omurova; V. V. Barinov; O. V. Kardash; E. A. Vaganov; V. S. Myglan; Г. Т. Омурова; В. В. Баринов; О. В. Кардаш; Е. А. Ваганов; В. С. Мыглан (Archaeology, Ethnology & Anthropology of Eurasia, 2018)
This study addresses the occurrence of damage to the anatomical structure (frost rings, light rings, and fluctuations of the wood density) and missing tree rings in wood samples from Fort Nadym—a medieval fort in the subarctic zone of Western Siberia. The chronology of extreme climatic events was reconstructed for the 1170–1505 period. We used multiple criteria such as severity of events; coincidence of structural pathologies and missing annual rings across all species; coincidence of structural anomalies with missing rings in specifi c years and years of minimum growth in chronologies. These criteria have allowed us to identify eight signifi cant climatic events for the study area. The comparison of information on those events with that relating to other regions has shown that the 1259 event, evidenced by various sources, was likely global. Two other events, 1342 and 1466, are registered in northwestern Siberia and North America, and are therefore inter-regional. The 1347 and 1440 events concerned only northwestern Siberia. These years coincide with those of documented volcanic eruptions, peaks of acidity and aerosol development in polar ice cores, as well as the historical accounts of severe cold, crop failure, etc. All these events had a strong impact on socio-economic processes in Western Siberia. В работе проведен анализ встречаемости нарушений анатомической структуры (морозобойные и светлые кольца, флуктуации плотности структуры древесины) и выпавших годичных колец в образцах древесины cо средневекового археологического памятника Надымский городок, расположенного в субарктической зоне Западной Сибири. В результате построена хронология экстремальных климатических событий, охватывающая период с 1170 по 1505 г. В ходе исследования был применен комплексный подход, основанный на привлечении таких параметров, как выраженность экстремального события, синхронность образования аномалий структуры и выпавших годичных колец у всех анализируемых древесных пород; годы, на которые приходятся как аномалии структуры, так ...